Right Unilateral Spatial Neglect Improves with Intrinsic Motivation - Hirotaka Saito; Haruka Kobayashi; Junichi Yatsu; Shigeru Obayashi (Case Reports in Neurological Medicine)
Background. In the acute phase of stroke, it is well known that the incidence and severity of unilateral spatial neglect (USN) are more significant in the right hemisphere injuries. Still, the detection of USN in left hemisphere injuries has been increasing in recent years. This trend is because behavioral assessments have prevented the exclusion of patients who are difficult to assess for USN or apathy using conventional paper-and-pencil tests (e.g., aphasia). Right USN and post-stroke apathy share many common lesions. Therefore, clinical symptoms may overlap, but little validation considers this. Case Study. A man (62 years old) determined to have the right USN and apathy was treated for six weeks in 3 terms. In the first term (weeks 1 to 2), the patient was treated for the right USN by conventional therapy. In the second term (3–4 weeks), treatment for right USN and apathy by goal-directed therapy based on affinity behavior was implemented. In the third term (5–6 weeks), goal-directed therapy based on affinity behavior was discontinued, and treatment was returned to conventional therapy only. In the second term (goal-directed therapy based on affinity behavior), the improvement in patients’ apathy (clinical assessment for spontaneity) was more significant than the effect size in the third term (conventional therapy). There were no significant differences in USN (catherine bergego scale) and intrinsic motivation (pittsburgh rehabilitation participation scale). However, the effect size in the second term tended to be larger than in the third term (conventional therapy). Clinical Rehabilitation Impact. This report aims to demonstrate the limitations of current treatment for cases determined to have both right USN and apathy. Second, to assess the extent to which this new intervention can complement the limitations of current treatment.